Techno-Economic and Risk Assessment of Small-Scale LNG Distribution for Replacing Diesel Fuel in Nusa Tenggara Region - Sommeng, Andy Noorsaman; Usman, Usman; Kurnianto, Jonathan (International Journal of Energy Economics and Policy, 2023)
The conversion of existing diesel-fuel power plants in remote areas of Indonesia to gas is a practical solution for the reduction of carbon emissions. However, the transportation of natural gas from its sources to plant gates across the vast and dispersed islands of the Indonesian archipelago using small-scale Liquefied Natural Gas (LNG) poses challenges in terms of economics and investment risks. Therefore, this study aims to analyze the techno-economic risks of converting diesel power plants spread across the Nusa Tenggara region to gas with acceptable prices. The real options method is applied to perform the economic evaluation based on a proposed cost-effective LNG distribution scheme. The gas demand from eight power plants with a total capacity of 347 MW across the region is 9,176 BBTU annually. The profitability analysis is carried out using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), and Profitability Index (PI) values showing USD 56,876,674, 15.3%, 7.25 years, and 1.48, respectively. The risk analysis using the real options method suggests that the investment risk is lower if the program starts in the first year with 20 years of operation. The use of gas lowers the cost of generation per kilowatt-hour and reduces carbon emissions compared to diesel-fueled power plants.